2001
DOI: 10.1161/hc4101.097419
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Neutrophil Collagenase (Matrix Metalloproteinase-8) in Human Atheroma

Abstract: Background-Loss of interstitial collagen, particularly type I collagen, the major load-bearing molecule of atherosclerotic plaques, renders atheroma prone to rupture. Initiation of collagen breakdown requires interstitial collagenases, a matrix metalloproteinase (MMP) subfamily consisting of MMP-1, MMP-8, and MMP-13. Previous work demonstrated the overexpression of MMP-1 and MMP-13 in human atheroma. However, no study has yet evaluated the expression of MMP-8, known as "neutrophil collagenase," the enzyme that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
203
1
8

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 301 publications
(218 citation statements)
references
References 34 publications
6
203
1
8
Order By: Relevance
“…5 Experiments used fresh monocytes or macrophages differentiated in culture in RPMI with 2% human serum (Sigma) for 3 to 10 days; 24 hours before and during stimulation, cells were incubated in serum-free media as previously described. 5,21 Venous blood was diluted 9:1 with 4% sodium citrate (Sigma) for neutrophil isolation. Cells were separated on neutrophil isolation medium gradients (Cardinal Associates Inc) and red cells were lysed with 155 mmol/L NH 4 Cl, 20 mmol/L NaHCO 3 , and 166 mol/L EDTA.…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…5 Experiments used fresh monocytes or macrophages differentiated in culture in RPMI with 2% human serum (Sigma) for 3 to 10 days; 24 hours before and during stimulation, cells were incubated in serum-free media as previously described. 5,21 Venous blood was diluted 9:1 with 4% sodium citrate (Sigma) for neutrophil isolation. Cells were separated on neutrophil isolation medium gradients (Cardinal Associates Inc) and red cells were lysed with 155 mmol/L NH 4 Cl, 20 mmol/L NaHCO 3 , and 166 mol/L EDTA.…”
Section: Cell Culturementioning
confidence: 99%
“…[2][3][4] We recently demonstrated that nonmyeloid cells found in atheroma express MMP-8, a collagenase previously associated with neutrophils. 5 This finding suggested to us that neutrophil elastase (NE) might also play a broader role than its name implies.…”
mentioning
confidence: 95%
“…The amounts of both total and active MMP-8 are significantly higher in ruptured infarct tissue in patients with fatal myocardial infarction compared to the control infarct tissue [12]. Production of MMP-8 may reflect the disease state, since its activity is higher in asymptomatic patients with plaque progression or plaques prone to rupture compared to those with a stable disease [6,13]. The association of serum or plasma MMP-8 concentrations with cardiovascular diseases is, however, somewhat conflicting and rarely reported.…”
Section: Introductionmentioning
confidence: 98%
“…The fibrous cap of the atherosclerotic plaque is rich in collagen, which the MMPs secreted by the local macrophages can degrade. MMPs localize especially in the shoulder regions of the cap; this area is the most vulnerable to rupture resulting in thrombosis [5,6]. MMPs are endogenously inhibited by the specific tissue inhibitor of metalloproteinases (TIMP), which binds to the active MMP at a molar equivalence [7].…”
Section: Introductionmentioning
confidence: 99%
“…Впливаючи на біоактивні нематриксні молекули, вона може модифікувати імунну відповідь і брати участь у захисних протизапальних процесах [32 ˗ 37]. У дослідженнях in vitro [38] було пока-зано, що ендотеліальні клітини, макрофаги, ГМК у ділянці атеросклеротичних уражень експресують ММР-8 після стимулювання прозапальними цитокінами: IL-1β, ФНП-α, CD40, її експресія зростає в разі швидкого прогресування ушкодження. Сироватковий вміст ММР-8 асоційований із наявністю атеросклерозу [39,40], розвитком нес-табільності АСБ [41,42], ГКС [43] та із несприятливим серцево-судинним прогнозом [44].…”
Section: вступunclassified